Promoting stress and anxiety recovery in older adults: assessing the therapeutic influence of biophilic green walls and outdoor view - Su Xiaoxue; Xuan Huang (Frontiers Media S.A., 2024)
Previous research has already provided evidence regarding the favorable impact of green walls and outdoor views on stress reduction and anxiety alleviation. However, there has been limited exploration into the combined effects of green walls and outdoor views on older adults. In this study, a between-subjects experiment was conducted using virtual reality (VR) technology with 23 participants. Following exposure to stressors, each participant underwent four randomized sessions, each lasting 5 min, in various virtual reality (VR) environments, encompassing non-biophilic and biophilic environments (including green walls, outdoor views, and their combination). Throughout the process, we measured physiological indicators of stress responses, including heart rate, heart rate variability, skin conductance levels, and blood pressure, using biometric sensors. Psychological changes in participants, including anxiety levels, were evaluated through the State-Trait Anxiety Inventory, recovery scales, and self-reported emotional assessments. In conclusion, in comparison to non-biophilic environments, older adults consistently exhibited lower stress levels, experienced superior anxiety relief, and demonstrated improved recovery in nature connectedness environments, with a notably faster recovery rate. These findings suggest that the incorporation of nature connectedness principles into the indoor environments of public activity spaces within older adults care facilities can significantly contribute to stress reduction and anxiety alleviation among older adults. Furthermore, these effects appear to be contingent on the specific types of nature connectedness environments. These results can provide substantial evidence to support the design of indoor common activity spaces within older adults care facilities.